O lugar do município no ensino de geografia - Bussolaro, Bernadete (2013)
This dissertation deals with the study of the place in the first series of Elementary School I, in order to reflect upon the reality of the school, especially on the geographical aspects of the city, being Francisco Beltrão the research field and the focus on the 4th year of Elementary School. The main factor for the development of the research was the problem faced while teacher, for seventeen years, in finding support material for working local Geography. The existing and donated material by the Municipal Department of Education is not sufficient to base the educator. There is great difficulty to find maps that show the Geography of the county, in physical, economic or environmental aspects. This research had as objective to search the possibilities and limits for working the geographical aspects of Francisco Beltrão in Geography teaching in the 4th year of the Elementary School I. To this objective, we propose to raise and examine the didactic material existing in schools to work the local Geography and from this point, we used as methodological procedures: research on the historical-geographical data of the city with the analysis of the didactic material in the years 1986, 2002, 2007; interview with the 4th year‟s subject teachers and the subject teachers who helped in the preparation of the textbooks in a total of twenty-five; analysis of the survey/interview; preparation of didactic sequence; we introduced didactic material to the teachers who evaluated it; we have systemized the teacher‟s analysis; and we elaborated material. Geography, in the first series, has as a function to contribute to teach geographically the students, enabling them to develop understanding to observe, read and understand the geographic space. The study of cartographic language, at the beginning of schooling, contributes to the students to develop skills relating to the understanding of the representation of space. It is of utmost importance that the child develops, since the initial series, the abilities of reading and interpreting maps, to better understand the relationships that are established in the social. The maps, in addition to localize, allow several interpretations, problematization and critical analysis, besides to raise actual hypotheses about the origin of a landscape. The reading of the lived area aims to create meanings for space and questions that allow the knowledge. The map is a means of communication that enables the establishment of linkage of empirical knowledge with the integrative analyzes, that contemplates the particular with the universal and vice versa. Students learn, with the geographic analysis, how to know their world, the place where they live, and are able to understand what are the processes of social exclusion and the selectivity of the spaces. By Studying their city, the region, the student will learn the process of formation and transformation. For the Geography teaching, a way to contemplate the knowledge of local reality is the cartographic representation, because the maps develop, when understood, critical view of what is represented.